2021
DOI: 10.4103/0973-029x.325252
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of pomegranate extract, sodium hypochlorite, chlorhexidine, Myrrh (Commiphora molmol), tulsi extract against Enterococcus faecalis, Fusobacterium nucleatum and Staphylococci epidermidis

Abstract: Background: The presence of pathogenic bacteria, toxins and byproducts in the root canal system show a decisive part in success of endodontic therapy. Thus, the complete removal of this bacterium is highly desirable. Several intracanal medicaments were tried to disinfect the root canal before obturation. Aim: The present study was conducted to compare Pomegranate, sodium hypochlorite, Chlorhexidine, Myrrh (Commiphora molmol), tulsi extract against Enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Rodrigues et al [ 36 ] observed similar results with the use of 2.5% NaOCl in relation to intratubular antimicrobial activity when compared to 2% CLX. This same difference was verified in previous studies [ 7 , 37 , 38 ] that compared the decontamination capacity of the canals by the two solutions.…”
Section: Discussionsupporting
confidence: 87%
“…Rodrigues et al [ 36 ] observed similar results with the use of 2.5% NaOCl in relation to intratubular antimicrobial activity when compared to 2% CLX. This same difference was verified in previous studies [ 7 , 37 , 38 ] that compared the decontamination capacity of the canals by the two solutions.…”
Section: Discussionsupporting
confidence: 87%